2020
DOI: 10.3389/fnagi.2020.00178
|View full text |Cite
|
Sign up to set email alerts
|

Voxel-Based Morphometry Reveals a Correlation Between Bone Mineral Density Loss and Reduced Cortical Gray Matter Volume in Alzheimer’s Disease

Abstract: Background: Decreased bone mineral density (BMD) was associated with poorer cognitive function and increased risk of Alzheimer's disease (AD). However, objective evidence for the relationship between osteoporosis and AD in humans has not been extensively described.Objectives: We aimed to evaluate the relationships between BMD and the cortical volumes of brain regions vulnerable to AD; hippocampus, parahippocampal gyrus, precuneus, posterior cingulate, and angular gyrus, using voxel-based morphometry (VBM), to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Further, we calculated the ASL data using the AW4.6 GE workstation to calculate the CBF map. Using the SPM8 software package applied in MATLAB, we initially registered the CBF image of each participant to their T1 image, normalized it to the standard brain, and lastly adopted an 8-mm isotropic Gaussian kernel for smoothing ( Takano et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Further, we calculated the ASL data using the AW4.6 GE workstation to calculate the CBF map. Using the SPM8 software package applied in MATLAB, we initially registered the CBF image of each participant to their T1 image, normalized it to the standard brain, and lastly adopted an 8-mm isotropic Gaussian kernel for smoothing ( Takano et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Prior research has indicated that bone loss is interconnected with alterations in the structure of the brain (56)(57)(58)(59)(60). We chose the DLPFC as the stimulating brain area based on the preliminary results of our clinical study of neuroimaging.…”
Section: Stimulating Location Of Intervention Modalities For Pmopmentioning
confidence: 99%
“…In particular, it is hypothesized that the “bone-brain crosstalk” relies on the secretion of some osteoblast-derived molecules from the bone to the blood that, in turn, can influence the brain development and normal function of the central nervous system if they pass the blood-brain barrier [ 18 , 19 ]. In addition, previous studies provide evidence that a link between BMD values (being measured by dual-energy X-ray absorptiometry [DXA]) and whole-brain volume (being measured by magnetic resonance imaging in AD) exists [ 20 , 21 ], suggesting that bone loss may play an important role in the AD-related neurodegeneration. Hence, abnormal BMD may be a potential indicator to identify participants with a high risk of AD.…”
Section: Introductionmentioning
confidence: 99%